A SYSTEMATIC LITERATURE REVIEW ON THE ROLE OF ENGLISH EXPOSURE IN DEVELOPING JUNIOR HIGH SCHOOL STUDENTS’ SPEAKING SKILLS: English - Niken Ayu Pramudita; Nailul Authar; Novi Rahmania Aquariza; Savira Zaniar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speaking is considered one of the most important language skills in English as a Foreign Language (EFL) learning because it enables students to express ideas and communicate effectively. However, many junior high school students still experience difficulties in developing speaking skills due to limited opportunities to use English in their learning environment. One important factor that supports language development is exposure to the target language. Therefore, this study aims to identify the types of English exposure used in speaking learning and examine how English exposure contributes to the development of junior high school students’ speaking skills. This study employed a Systematic Literature Review (SLR) to analyze relevant previous studies related to English exposure and speaking skills. A total of 10 studies published between 2017 and 2026 were selected and analyzed based on specific inclusion criteria. The findings reveal that English exposure in speaking learning occurs through several instructional approaches, including role-play activities, technology-based learning media, and interactive classroom activities such as picture-based tasks and problem-based learning. These forms of exposure provide students with meaningful opportunities to practice speaking, increase their confidence, and improve their communication performance. Overall, the results indicate that English exposure plays a significant role in supporting the development of junior high school students’ speaking skills. Providing varied and meaningful exposure to English can help students develop greater confidence, fluency, and communicative competence in speaking.